KEPUTUSAN PEMBELIAN E-COMMERCE MELALUI KEMUDAHAN PENGGUNAAN, KUALITAS INFORMASI DAN KUALITAS INTERAKSI LAYANAN WEB - Siti Romla; Alifah Ratnawati (Jurnal Ekonomi dan Bisnis, 2018)
Purchasing decisions become an important thing in retaining customers. The purchase decisionis a customer’s response to a discrepancy between the level of prior importance and the actualperformance it perceives after use. As for the population is a student class of 2013. Samplestaken in the study obtained for 96.04 then rounded up to 100 people. Based on the abovecalculation results, the number of samples taken in this study is the student class of 2013as many as 100 respondents. Criteria of sampling as a resource is a social networking siteusers who have made purchases two (2) times through social networking sites. The result ofresearch indicate that Ease, Quality of information, Quality of interaction have positive andsignificant influence to trust, Ease, Quality of information, Quality of interaction have positiveand significant influence to purchasing decision, Trust influence positively and significantly topurchasing decision.Keywords : Ease, Quality of information, Quality of trust interaction, purchase decision